2018
DOI: 10.1111/all.13432
|View full text |Cite
|
Sign up to set email alerts
|

Association of STAT6 gene variants with food allergy diagnosed by double‐blind placebo‐controlled food challenges

Abstract: This study describes the role of two STAT6 gene variants in food allergy using data of patients and their parents who underwent double‐blind placebo‐controlled food challenges (DBPCFCs). After quality control, 369 trios were analysed including 262 children (71.0%) with food allergy. Associations were tested by the Family based association test. The A alleles of both SNPs were associated with food allergy (P = .036 and P = .013 for rs324015 and rs1059513, respectively). Furthermore, these A alleles were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…110 The role of the STAT6 gene variants in patients with FA is further supported by association of the specific SNPs in the STAT6 gene with more severe symptoms during food challenges. 111 Similar to the GWAS analysis, 104 the candidate-gene analysis identified FLG as a common risk factor for AD and FA, again reinforcing the importance of barrier integrity. 109 Collectively, these data show significant functional overlap between patients with FA and those with EoE in several genes linked to the epithelial barrier, type 2 response, and protease activity, yet some associations, such as CAPN14, remain specific to EoE, emphasizing the role of esophageal epithelial genes in the pathophysiology of EoE (Fig 3).…”
Section: Genetic and Epigenetic Mechanisms In Epithelial Responses Inmentioning
confidence: 79%
See 2 more Smart Citations
“…110 The role of the STAT6 gene variants in patients with FA is further supported by association of the specific SNPs in the STAT6 gene with more severe symptoms during food challenges. 111 Similar to the GWAS analysis, 104 the candidate-gene analysis identified FLG as a common risk factor for AD and FA, again reinforcing the importance of barrier integrity. 109 Collectively, these data show significant functional overlap between patients with FA and those with EoE in several genes linked to the epithelial barrier, type 2 response, and protease activity, yet some associations, such as CAPN14, remain specific to EoE, emphasizing the role of esophageal epithelial genes in the pathophysiology of EoE (Fig 3).…”
Section: Genetic and Epigenetic Mechanisms In Epithelial Responses Inmentioning
confidence: 79%
“…109 Collectively, these data show significant functional overlap between patients with FA and those with EoE in several genes linked to the epithelial barrier, type 2 response, and protease activity, yet some associations, such as CAPN14, remain specific to EoE, emphasizing the role of esophageal epithelial genes in the pathophysiology of EoE (Fig 3). [28][29][30]34,55,[101][102][103][104]109,111…”
Section: Genetic and Epigenetic Mechanisms In Epithelial Responses Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with genomics, multiple different technologies have been categorized, with eight showing great promise for biomarker discovery of AIT success (Table 1). 43 Genomics can be applied for discovery of genetic variants, including rare ones in patients with inborn errors of immunity (IEI) where these are causative for the phenotype 44,45 and more common variants that predispose to atopy 44,46,47 or affect asthma severity. 48 If genetic variants that affect the response to AIT are identified, these could potentially be used at baseline to stratify patients.…”
Section: Technolog Ic Al Advan Ce S For Identific Ation Of B Iomarkmentioning
confidence: 99%
“…There are several established gene variants that have been shown to directly result in allergic disease in hyper-IgE syndrome (STAT3, DOCK8, PGM3, ERBIN, IL6ST and CARD11) 80 or in Netherton syndrome (SPINK5), 81 and others that have been shown to predispose to disease (STAT6, FGN). 46,82 In addition, for more than a decade, genome-wide association studies have revealed many genes in which variants are highly associated with allergic disease. 83,84 With the data sets getting larger, the resolution of this approach has improved, resulting in a limited number of genes that are now reproducibly found and shared between allergic diseases.…”
Section: Genetic Variantsmentioning
confidence: 99%